2019
DOI: 10.12669/pjms.35.6.788
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the predicted accuracy of PO2\FIO2 ratio with rapid shallow breathing index for successful spontaneous breathing trial in Intensive Care Unit

Abstract: Objective: To compare the predicted accuracy of PFR with RSBI for successful spontaneous breathing trail before extubation in intensive care unit. Methods: This cross sectional study was conducted at the ICU of Ch. Pervaiz Ellahi Institute of Cardiology, Multan Medical and Nishtar Medical University Hospital from July, 2017 to January, 2019. PO2/FIO2 and RSBI was measured by a different investigator, before and 20 minutes after the start of SBT. Heart rate, blood pressure and oxygen saturation were conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Segal concluded that RSBI variability as a dynamic change marker can improve prediction offline ability (18). Furqan et al found that a RSBI threshold of less than 105 can more accurately predict the successful weaning of patients in ICUs (19). However, the results of some related studies (20) did not support these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Segal concluded that RSBI variability as a dynamic change marker can improve prediction offline ability (18). Furqan et al found that a RSBI threshold of less than 105 can more accurately predict the successful weaning of patients in ICUs (19). However, the results of some related studies (20) did not support these findings.…”
Section: Discussionmentioning
confidence: 99%